Helicopter emergency medical services in Eastern Iran: a 4-year cross-sectional study of time intervals and mission profiles - Mohammad Hossein Esmaeilzadeh; Akram Nami; Razyeh Bajoulvand; Toktam Paykani (BMC Emergency Medicine)
Abstract Background Air medical transport services play a significant role in emergency situations by providing timely transfers of critically ill patients to medical facilities. This study aimed to investigate the mission characteristics of helicopter emergency medical services (HEMS) and the associated time intervals in a geographically remote region of eastern Iran. We also compared the prehospital times of HEMS and ground transportation to determine whether dispatching a helicopter is time-efficient. Methods This retrospective cross-sectional study was conducted at the prehospital emergency medical center in Gonabad, a remote area in eastern Iran. Data were collected using standardized electronic forms developed by the Ministry of Health and Medical Education (MOHME) in Iran. We analyzed the mission profiles and prehospital time intervals for all Gonabad HEMS missions conducted between 2021 and 2024. The mean activation time was compared to the national benchmark of three minutes, and the prehospital time intervals of air ambulances were compared to those of ground ambulances. Results From 2021 to 2024, there were 252 HEMS missions, transporting 265 patients. Of all 252 missions, 95 (37.7%) were primary missions, and 157 (62.3%) were secondary missions. The most frequent reasons for air ambulance dispatch were trauma, acute coronary syndrome, and strokes. The mean ± SD for HEMS activation time was 9.14 ± 3.63 min, significantly exceeding the national benchmark of three minutes. HEMS prehospital time was 49.73 ± 9.67 min. The comparison of prehospital time intervals indicated that air emergency services are more time-efficient than ground ambulances. Conclusion This study found that the mean activation time of air ambulances exceeded the national benchmark of three minutes. When comparing prehospital times for air ambulance and ground ambulance services, HEMS was faster than both ground scenarios. The current benchmark for helicopter activation time in Iran may need clarification and revision.